Hydrodynamics and Sediment Mobility Processes Over a Degraded Senile Coral Reef. Issue 10 (4th October 2018) - Torres‐Garcia, Legna M.; Dalyander, P. Soupy; Long, Joseph W.; Zawada, David G.; Yates, Kimberly K.; Moore, Christopher; Olabarrieta, Maitane
Abstract: Coral reefs can influence hydrodynamics and morphodynamics by dissipating and refracting incident wave energy, modifying circulation patterns, and altering sediment transport pathways. In this study, the sediment and hydrodynamic response of a senile (dead) barrier reef (Crocker Reef, located in the upper portion of the Florida Reef Tract) to storms and quiescent conditions was evaluated using field observations and the Coupled Ocean‐Atmosphere‐Wave‐Sediment Transport model. Waves, circulation, and resultant sediment mobility were modeled across different reef zones. Sediment mobility during quiescent periods and the passage of far‐field storms are driven by nonbreaking waves and, to a lesser degree, regional circulation. Spatial variability in these processes produces the present‐day distribution of sediment grain size at Crocker Reef, wherein finer‐grain material along a shallow central ridge is frequently mobilized (43% to 62% of the time), winnowed away, and deposited along the lower‐energy flanks and in the fore reef where sand mobility occurs less frequently (32% to 43% and 1% to 22% of the time, respectively). Analysis of wave conditions for the period of 2006–2014 supports that wave heights rarely exceed the threshold for breaking (0.1% and 0.3% at the reef crest and at the reef flat, respectively), predominantly during the passage of tropical storms. There is a shift to a wave‐breaking regime during near‐field storms, creating the potential for mobilization of larger material and enhanced reef degradation. Sediment mobility can be enhanced due to wave skewness or the generation of free infragravity waves during periods of depth‐induced wave breaking. Key Points: Wave energy dissipation on a degraded reef is dominated by wave breaking during near‐field storms and through bottom friction otherwise Spatial variability in sediment grain size (sand to gravel) is identified and correlated to modeled shear stress variability Sand is frequently resuspended, whereas mobility of reef gravel is confined to higher‐energy storm events